String Instruments: Bowed - Jane Beethoven; Rosanne Emery; Cliff Lenz (Music magic video library, 1991)
Viewers see and hear world-class performances on bowed string instruments - - Discover the erhu, a bowed string instrument from China - - Enjoy some country fiddling - - See and hear an extraordinary young violinist perform at ages 3, 9, and 12 - - See performances by famous virtuosi.